EVALUASI PELEPASAN INFORMASI KESEHATAN DENGAN METODE CIPP - Atika Mima Amalin; Novita Nuraini (Jurnal Infokes, 2022)
The release of health information to third parties must use a power of attorney. The release of health information without using a power of attorney can have a negative impact. Power of attorney is needed so that there is no deviation in the provision of claims submitted by health service providers to the insurance company. The purpose of the study was to determine the suitability of information release activities from activity planning, strategies used in achieving goals, process of information release activities and success of health information release activities. This study uses the CIPP evaluation method, namely evaluating information release activities from the context, input, process and product aspects. Data was collected by observation, interviews and documentation. The results of the study indicate that there is a discrepancy between the release of information activities with the regulation of the minister of health. Inconsistency in the purpose of releasing information which is only for insurance, in its activities it was found that there was no power of attorney in requesting health information 44%, there was no clear name of the doctor 12.5% and there was no information on filling time of 36.5%. The decision obtained from the evaluation results is to modify the goals, objectives and strategies to achieve the goals. The final decision was to continue the information release activity by revising the SOP. The solution obtained from the discussion is the SOP for the release of health information that can be used for third parties in general. Revised SOP for releasing existing information with additional points regarding power of attorney and completeness of filling out.